Split-hand index: A diagnostic and prognostic marker in amyotrophic lateral sclerosis across varying regions of onset. Issue 9 (September 2021) - Hannaford, Andrew; Higashihara, Mana; Pavey, Nathan; van den Bos, Mehdi; Geevasinga, Nimeshan; Vucic, Steve; Menon, Parvathi
Highlights: The split-hand index (SI) was assessed on both sides in a large cohort of ALS patient of varying clinical subtypes. The SI was significantly reduced on both sides but most significantly in Awaji definite/probable and in upper limb onset ALS. SI strongly correlates with clinical measurements, ALSFRS-R, neurophysiological index and significantly reduces on progress study. Abstract: Objective: The split-hand index (SI), a reliable diagnostic marker of amyotrophic lateral sclerosis (ALS), was prospectively assessed for differences across ALS subtypes and between the onset side of clinical symptoms or the dominant and contralateral sides. In addition, the prognostic utility of the SI was longitudinally assessed. Methods: Two hundred and forty-five ALS patients underwent measurement of SI on both sides compared with 126 neuromuscular mimic disorders (NMD). A subset of patients (N = 45) underwent longitudinal assessment of SI. Results: The SI was significantly reduced (SI RIGHT ALS 5.47(4.2), SINMD 9.0 (5.0); P < 0.001; SILEFT ALS 5.5 (4.1), SI NMD 9.4 (5.0), P < 0.001) on both sides in all ALS patients with prominent reduction on the onset side in upper limb onset ALS (SI RIGHT P < 0.001; SI LEFT P < 0.05) and in Awaji definite/probable diagnostic category (SI RIGHT P < 0.05; SI LEFT P < 0.05). Longitudinal studies disclosed that the rate of SI decline correlated with the decline in ALSFRS-R (r = 0.21, P < 0.05). Conclusion: The SI is reduced in all ALS subtypes most prominently in upper limb onset disease, on the side of clinical onset, and in patients with Awaji definite/probable diagnostic category. Significance: The split-hand index is a reliable diagnostic and outcome biomarker across ALS subtypes and may have potential utility in a clinical trial setting, although further multicenter studies are required to confirm this.